DECREASING OF NEONATAL MORTALITY AT UNIVERSITY GYNECOLOGY AND OBSTETRICS CLINIC IN SKOPJE- OUR MATERIAL - Bushinoska Ivanova, Gabriela; Ilieva, Maja Pejkovska; Bushinoska, Jasna; Ivanov, Jordancho (Journal of Morphological Sciences, 2026)
Neonatal mortality (NNM) is a mortality in newborns in the first 28 days after birth, or of newborns born after 22 weeks of gestation and with a birth weight greater than 500 g, per thousand live births. For many years, N. Macedonia and the University Gynecology and Obstetrics Clinic in Skopje (UGOC- Skopje), were between leaders in NNM in Europe. From 2018, the NNM in Macedonia and on UGOC- Skopje has started to decrease. Aim of the study: The aim of the paper is to present and compare the NNM figures in the Neonatal Intensive Care Unit (NICU) at UGOC- Skopje, in two different periods - the period when the NNM at the clinic was high from 2011-2017 and during 9 months study which was made in 2019-2020 on the same clinic, when the NNM rate began to fall significantly on the clinic and in the country. Material and methods: Several previously conducted retrospective studies on NNM at UGOC-  Skopje and one prospective study that lasted 9 months from May 2019 to the end of January 2020 were used to obtain and compare the results for NNM rate at the Clinic in this paper. Results: In 9 month study in 2019-2020, the NNM at the Clinic and in the country, began to record a significant decline. There is a significant decrease in NNM in the group of very premature newborns, born from 28-32 weeks of gestation compared to previous years 2011-2017. NNM rate has significantly decreased and in the group of newborns born with very low birth weight (from 1000-1499 g) and low birth weight (1500-2499 g) compared to previous years.Conclusion: The UGOC- Skopje and N. Macedonia have made progress in the last 5 years in reducing the NNM, which was one of the highest in Europe. This was helped by improved vital statistics, the use of the latest protocols for reducing NNM, and improved technical conditions at NICU. Key words: Gestational weeks- G.W., Low birth weight- LBW, Neonatal mortality- NNM, Neonatal Intensive Care Unit- NICU, North Macedonia.